Plasmonic Purcell effect reveals obliquely ordered phosphorescent emitters in Organic LEDs - Mac Ciarnain, R.; Michaelis, D.; Wehlus, T.; Rausch, A. F.; Wehrmeister, S.; Schmidt, T. D.; Bruetting, W.; Danz, Norbert; Braeuer, A.; Tuennermann, A. (Scientific Reports, 2017)
The non-isotropic alignment of molecules can increase the interaction efficiency with propagating light fields. This applies to both emissive and absorptive systems and can be exploited for achieving unprecedented efficiencies of organic opto-electronic devices such as organic light-emitting diodes. Optical analysis has revealed certain phosphorescent emitters to align spontaneously in an advantageous orientation. Unfortunately, established approaches only determine an average orientation because emission patterns solely depend on the second moments of the transition dipole vector distribution. In order to resolve further details of such a distribution, additional differences in the emission characteristics of parallel and perpendicularly oriented emitters need to be introduced. A thin metal layer near the emitters introduces plasmon mediated losses mostly for perpendicular emitters. Then, analyzing the emission at different polarizations allows one to measure emission lifetimes of mostly parallel or mostly perpendicular oriented emitters. This should alter the transient emission when observing the temporal phosphorescence decay under different directions and/or polarizations. The angular width of the orientation distribution can be derived from the degree of such lifetime splitting. Our results suggest a narrow but obliquely oriented molecular ensemble of Ir(MDQ)2(acac) doped into the α-NPD host inside an Organic LED stack.
CRIS-Team Scopus Importer:2023-04-20